Chapter Digital Sieves - Baert, Barbara (De Gruyter, 2019)
The subject of About Sieves and Sieving is the motif of the sieve, starting from the enigmatic portraits of Elizabeth I, Queen of England and Ireland (1533-1603). The sieve exhibits a wide range of meanings that extends across art history, philosophy, anthropology, psychoanalysis, and gender studies. This essay will provide an interdisciplinary perspective on the sieve from four angles of approach: motif, symbol, technique, and paradigm.